Carcinogenesis, The Role of Genetic Research in the Fight Against Cancer, Atlas of the Cancer Genome (International Journal of Psychosocial Rehabilitation, 2020)
The lecture is devoted to the role of genetic research in understanding carcinogenesis and finding the ways to treat cancer in the light of recent advances in medical genetics. The creation of a detailed catalogue of cancer genes is an important task, the accomplishment of which will allow us to select the optimal cancer therapy for each patient. To compile a catalogue of cancer genes mutating with high (>20%) and medium (2-20%) frequency, it is required to analyze 2,000 pairs of “tumor-norm” on average for each gene; that is about 100,000 pairs for the 50 most common types of cancer. Now, it no longer raises any insurmountable problem, as the cost of DNA sequencing has decreased a millionfold over the last 10 years and will continue to decrease.